(untitled) (Stamford Journal of Microbiology, 2015)
Multidrug-resistant tuberculosis (MDR-TB) has become one of the major public health menace in the developing countries which have destructive consequences in immunocompromised patients. Rapid detection of such cases is indispensable to initiate the early and proper treatment of the infected individuals. Present study was conducted to determine the frequency of drug resistant Mycobacterium tuberculosis among the TB suspected diabetic patients employing GeneXpert MTB/RIF method. A total of 1311 sputum specimens were tested among which 154 (11.7%), 109 (8.3%) and 92 (7%) were found to carry Mycobacterium tuberculosis by GeneXpert, auramine O staining and Zeihl-Neelsen (Z-N) staining methods, consecutively. The relative positivity of the GeneXpert method was 40.3% and 29.2% higher than that of Z-N and auramine O staining methods. The sensitivity, specificity and accuracy of GeneXpert method were found to be higher when compared to these microscopic techniques. An estimation of 12.9% (n=132) of the positive cases was found among the diabetic patients (n=1027), whereas 7.7% (n=22) of the non-diabetic patients (n=284) showed positivity by GeneXpert method. Four (2.6%) among the MTB positive cases exhibited rifampicin resistance of which 3 were diabetic patients. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22754 Stamford Journal of Microbiology, Vol.4(1) 2014: 9-12